Kesulitan Siswa dalam Menghafal Ayat di SMP Negeri 2 Sungai Pua - Hasibuan, Irma Dhani; Ilmi, Darul (Lembaga Yasin AlSys, 2023)
The difficulty of memorizing verses of the Qur'an is a situation that makes it difficult for students to embed memorized verse material into memory when recalling verses that have been memorized. The research objectives were to find out: 1) Students' difficulties in memorizing verses at Sungai Pua 2 Public Middle School, 2) Supporting factors and obstacles in memorizing Al-Qur'an verses at Sungai Pua 2 Public Middle School. The research method is qualitative with observational data collection techniques, interviews with school principals, Islamic religious education teachers and several students as well as documentation. Based on the results of the study it can be seen that: 1) students' difficulties in memorizing verses of the Al-Qur'an. : a) the appearance of laziness in the memorizer. b) Students lack focus and concentration. c) when you experience this, the mind will be overstimulated (distracted), thus reducing the ability to remember. 2) Supporting factors and obstacles in memorizing verses of the Qur'an for second grade students at SMP N 2 Sungai Pua. There is support from parents and Islamic religion teachers and there is cohesiveness to motivate students to always memorize verses so that there are no mistakes when depositing verses those who have memorized, to know and understand the meaning or meaning contained in the verses of the Qur'an a) cannot divide the time properly, forget about similar verses. b) love disturbances, difficulty repeating memorization, weakening enthusiasm for memorizing, and not being consistent in memorizing verses of the Qur'an.